Challenging assumptions about the demographics of eosinophilic gastrointestinal diseases: A systematic review - Mirna Chehade, MD, MPH; Benjamin L. Wright, MD; Samantha Walsh, MLS, MA; Dominique D. Bailey, MD; Amanda B. Muir, MD; Amy D. Klion, MD; Margaret H. Collins, MD; Carla M. Davis, MD; Glenn T. Furuta, MD; Sandeep Gupta, MD; Paneez Khoury, MD; Kathryn A. Peterson, MD; et al. (Journal of Allergy and Clinical Immunology: Global, 2024)
Background: The demographic characteristics of patients with eosinophilic gastrointestinal diseases (EGIDs) are poorly understood. Population-based assessments of EGID demographics may indicate health disparities in diagnosis. Objectives: We aimed to characterize the demographic distribution of EGIDs and evaluate the potential for bias in reporting patient characteristics. Methods: We conducted a systematic review, extracting data on age, sex, gender, race, ethnicity, body mass index, insurance, and urban/rural residence on EGID patients and the source population. Differences in proportions were assessed by chi-square tests. Demographic reporting was compared to recent guidelines. Results: Among 50 studies that met inclusion/exclusion criteria, 12 reported ≥1 demographic feature in both EGID and source populations. Except for age and sex or gender, demographics were rarely described (race = 4, ethnicity = 1, insurance = 1) or were not described (body mass index, urban/rural residence). A higher proportion of male subjects was observed for EoE or esophageal eosinophilia relative to the source population, but no difference in gender or sex distribution was observed for other EGIDs. “Sex” and “gender” were used interchangeably, and frequently only the male proportion was reported. Reporting of race and ethnicity was inconsistent with guidelines. Conclusion: Current data support a male predominance for EoE only. Evidence was insufficient to support enrichment of EGIDs in any particular racial, ethnic, or other demographic group. Population-based studies presenting demographics on both cases and source populations are needed. Implementation of guidelines for more inclusive reporting of demographic characteristics is crucial to prevent disparities in timely diagnosis and management of patients with EGIDs.